Elevated plasma phospholipid n-3 docosapentaenoic acid concentrations during hibernation - Strandvik, Birgitta (Karolinska Institutet Neo); Giroud, Sylvain (University of Veterinary Medicine Vienna); Stenvinkel, Peter (Karolinska Institutet); Kindberg, Jonas (Swedish University of Agricultural Sciences / Norwegian Institute for Nature Research); Fröbert, Ole (Örebro University / Aarhus University / Aarhus University Hospital); Engvall, Martin (Karolinska Institutet); Backman-Johansson, Carolina (Karolinska Institutet); Qureshi, Abdul Rashid (Karolinska Institutet); Painer, Johanna (University of Veterinary Medicine Vienna) (PLOS ONE, 2023)
Factors for initiating hibernation are unknown, but the condition shares some metabolic similarities with consciousness/sleep, which has been associated with n-3 fatty acids in humans. We investigated plasma phospholipid fatty acid profiles during hibernation and summer in free-ranging brown bears (Ursus arctos) and in captive garden dormice (Eliomys quercinus) contrasting in their hibernation patterns. The dormice received three different dietary fatty acid concentrations of linoleic acid (LA) (19%, 36% and 53%), with correspondingly decreased alpha-linolenic acid (ALA) (32%, 17% and 1.4%). Saturated and monounsaturated fatty acids showed small differences between summer and hibernation in both species. The dormice diet influenced n-6 fatty acids and eicosapentaenoic acid (EPA) concentrations in plasma phospholipids. Consistent differences between summer and hibernation in bears and dormice were decreased ALA and EPA and marked increase of n-3 docosapentaenoic acid and a minor increase of docosahexaenoic acid in parallel with several hundred percent increase of the activity index of elongase ELOVL2 transforming C20-22 fatty acids. The highest LA supply was unexpectantly associated with the highest transformation of the n-3 fatty acids. Similar fatty acid patterns in two contrasting hibernating species indicates a link to the hibernation phenotype and requires further studies in relation to consciousness and metabolism.